Mineralogical Approaches to Archaeological Materials Technological and Social Insights - Santacreu, Daniel; Carvajal López, José Cristóbal; Durán Benito, Adrián (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Archaeometry is based on the necessary interdisciplinary relationship between diverse branches of the natural and social sciences. This relationship is essential in archaeology, since, from physical materials (objects), scholars have to face questions that go beyond the limits of the tangible and pertain instead to abstract and social concerns. Currently, archaeometric studies are fundamental to the accurate classification and characterization of archaeological materials, providing relevant data, among other aspects, about their production, function and social meaning. In this book, we present a set of papers that show the potential of mineralogical studies (e.g. petrography, mineral geochemistry, X-ray Diffraction) and multiproxy approaches to characterize the composition of a wide diversity of archaeological materials such as ceramics, terracotta, tiles, metals, glazes, glass and mortars related to several periods (Bronze Age, Roman, Middle Age, Modern period). In this sense, this book can be of interest for specialized researchers who seek specific case studies and are mainly concerned with certain kinds of materials, but also for those students, researchers and professionals who look for a practical overview of the chief methods that can be followed in the study of material culture.